Wyznania, Rousseau i dyskurs edukacyjny – zarys badań w perspektywie (post)foucaultowskiej - Helena Ostrowicka (Problemy Wczesnej Edukacji)
The paper takes into consideration the Foucauldian concept of confession as an analytical category attractive for educational research. The article consists of three parts. Part one, based on Michel Foucault’s lectures at the Collége de France and “The History of Sexuality”, contains definitions of the key concepts: “the regime of truth” and “the regime of confession”. Part two provides an overview of selected studies in which the category of confession was used in the analyses of contemporary education. The last part refers to the Jean-Jacques Rousseau’s “Confessions” and presents selected aspects of research on educational discourse in the light of the concept of confession.